POTRET PERKAWINAN UMAT AGAMA BAHA’I DENGAN UU NOMOR 1 TAHUN 1974: STUDI KASUS DI PATI JAWA TENGAH - Moh Rosyid (Program Studi Hukum Keluarga Islam, 2016)
This article is based on field research among Baha‟i community in Pati, Central Java. According to Penpres No 1/PNPS/1965 there is no limitation of religion in Indonesia. However, some of regional officers in Pati still believe that there are only six official religions in Indonesia in which Baha‟i is excluded. Consequently, Baha‟i people who want to register their marriage is refused by the officials in the office of Civil Registration.